La restauration, la conservation et la valorisation du patrimoine technique semi-mobilier - Philippe Tomsin (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Semi-movable technical heritage refers to objects with volumes or masses which create problems and prohibitive costs when it is necessary to move them in a heritage context. These artefacts have many peculiarities: a wide variety of materials (some presenting health risks for restorers), very varied and sometimes specific alterations, special environmental conditions for conservation, difficulties and prohibitive costs of interventions. Sometimes, ordinary ethical rules in restoration are problematic to apply.